2009
DOI: 10.4076/1757-1626-2-8875
|View full text |Cite
|
Sign up to set email alerts
|

Primary lymphoma of the prostate treated with rituximab-based chemotherapy: a case report and review of the literature

Abstract: IntroductionPrimary lymphoma of the prostate is very rare. In this paper we present a case of early stage non-Hodgkin lymphoma of the prostate managed with six cycles of rituximab-based chemotherapy, and review the related literature.Case presentationAn 84-year-old man was admitted to our hospital having signs and symptoms suggestive of prostatic disease for 3 years. Histological and immunocytochemical studies of trans-urethral biopsy of the prostate showed diffuse large B-cell lymphoma. Radiological assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…2 These clinical features are significant in assisting the clinical diagnosis of PPL. Previous studies in the literature also reported the presence of prostate tumors and prostate hyperplasia on pelvic CT imaging, 6 which are consistent with the findings in our case. Compared with CT and magnetic resonance imaging (MRI), some researchers believe that ultrasound remains a helpful tool for the diagnosis of PPL.…”
Section: Discussionsupporting
confidence: 93%
“…2 These clinical features are significant in assisting the clinical diagnosis of PPL. Previous studies in the literature also reported the presence of prostate tumors and prostate hyperplasia on pelvic CT imaging, 6 which are consistent with the findings in our case. Compared with CT and magnetic resonance imaging (MRI), some researchers believe that ultrasound remains a helpful tool for the diagnosis of PPL.…”
Section: Discussionsupporting
confidence: 93%
“…Although the prognosis of primary lymphoma of the prostate was classically considered to be poor, some articles have suggested that prolonged survival could be expected if chemotherapy was administered. Taleb et al reported that combination chemotherapy with rituximab and CHOP was useful for the treatment of diffuse large B cell lymphoma of the prostate [6]. …”
Section: Discussionmentioning
confidence: 99%
“… 5 The prostate specific antigen (PSA) level is often within the normal range for non-hodgkins lymphomas. 3 , 6 , 7 , 8 For case reports specifically finding follicular lymphoma of the prostate, only Gorgel et al found a normal PSA of 2.4 ng/ml, with the other two cases both having elevated PSA levels. 8 Nerli et al (2020) presented a 73-year-old male with primary follicular lymphoma with a PSA of 46.83 ng/ml, and similarly Oosterheert et al reported a follicular NHL of the prostate with PSA of 62 ng/ml.…”
Section: Discussionmentioning
confidence: 99%